Pluralisme Masyarakat Adat Donggo Dalam Merawat Kerukunan Beragama - Haryanto, Lutfin; Oya, Abas; Atmaja, Jessy Parmawati (Lembaga Penelitian dan Pendidikan Mandala, 2021)
Pluralism is a view of life in understanding, acknowledging and accepting the existence of pluralism and diversity in a community group. The people of Donggo, Bima Regency, West Nusa Tenggara have different religious beliefs, in which there are different cultures and customs. There are three religions that developed in Palama Village 2, Nggerukopa hamlet, Donggo District, namely Islam, Catholicism and Protestantism. With a variety of religious beliefs, of course, each individual community has different desires, and this can lead to conflict between individuals in the community, for this reason it is necessary to understand pluralism which refers to the meaning of tolerance in order to live in harmony, to unite the diversity of a nation. The formulation of the problem raised in this study is how is the form of religious harmony in the Donggo custom community? The formulation of the problem raised. The purpose of this study is to find out the pluralism of the Donggo custom people in maintaining religious harmony. Researchers obtain data in this study is from observation, interviews and documentation. The data were analyzed by qualitative descriptive method. Based on the results of the study it was found that the forms of harmony of the Donggo custom people in maintaining religious harmony were cua kaco'i angi (mutual respect), doho kaboro weki (sitting together), inga dasa uma (helping to build a house), batu rawi rasa (participating in events) and tio kasama weki rasa ra dana (guarding with the village). Thus, the researcher concludes that the Donggo custom people in Nggerukopa really care for their religious harmony in any form to continue to live in harmony with each other.